2006
DOI: 10.1007/s00192-006-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vaginal and cesarean delivery on lower urinary tract symptoms: what makes the difference?

Abstract: A prospective cohort study was undertaken to evaluate the effect of pregnancy and childbirth in nulliparous pregnant women. The focus of this paper is on the difference in the prevalences and risk factors for lower urinary tract symptoms (LUTS) between woman who delivered vaginally or by cesarean and secondly the effect of LUTS on the quality of life between these two groups was analyzed. Included were 344 nulliparous pregnant women who completed four questionnaires with the Urogenital Distress Inventory and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
64
6
18

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 32 publications
15
64
6
18
Order By: Relevance
“…52 Some studies have shown a low impact on the quality of life of women with UI; however, they were conducted during pregnancy or in the first year postpartum. 53,54 This difference in results might be associated with the fact that the women in these situations see UI as an expected disorder for such situations instead of considering it a disease. Córcoles et al, studying 126 women with SUI, demonstrated impairment in their quality of life with gradual deterioration as they got older.…”
Section: Discussionmentioning
confidence: 95%
“…52 Some studies have shown a low impact on the quality of life of women with UI; however, they were conducted during pregnancy or in the first year postpartum. 53,54 This difference in results might be associated with the fact that the women in these situations see UI as an expected disorder for such situations instead of considering it a disease. Córcoles et al, studying 126 women with SUI, demonstrated impairment in their quality of life with gradual deterioration as they got older.…”
Section: Discussionmentioning
confidence: 95%
“…24 Fritel et al 25 concluíram que mulheres acima de 35 anos possuem maior risco de desenvolver disfunções do assoalho pélvico. Isso ocorre porque o envelhecimento fisiológico é acompanhado pelo aumento na densidade das fibras de desnervação da musculatura do assoalho pélvico (MAP), de modo que quanto maior a densidade, menor a velocidade da condução nervosa.…”
Section: Domíniosunclassified
“…24 No presente estudo, entre as gestantes com perda urinária, a maior proporção foi de secundigestas de parto vaginal anterior. No entanto, há evidências de que esses sintomas também ocorram em primigestas.…”
Section: Domíniosunclassified
“…Além da via de parto vaginal, alterações anatômicas e fisiológicas que ocorrem no trato urinário inferior ao longo da gestação predispõem o desencadeamento de SUI. Os SUI, decorrentes da gestação ou do trauma obstétrico, podem persistir após o parto 7,8 e gestações subseqüentes parecem atribuir risco adicional à disfunção do trato urinário inferior, aumentando a severidade dos sintomas urinários 9 . Scarpa et al 10 observaram que a paridade (multíparas ≥ 4) foi associada ao aumento de SUI, particularmente da noctúria e freqüência miccional, durante o último trimestre da gestação.…”
Section: Introductionunclassified
“…Primíparas, que tiveram parto via vaginal, apresentaram maior ocorrência da urgência e da urge-incontinência no puerpério, comparado às mulheres submetidas à cesariana. Entretanto, um ano depois do parto, esta diferença não se manteve significativa 8 . Assim como Chaliha et al 20 , neste estudo, não foi observada associação significativa entre a presença dos sintomas urinários irritativos após o parto e a via exclusiva de parto (vaginal ou cesárea).…”
Section: Introductionunclassified